1976
DOI: 10.1021/ac50007a014
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatographic quantitation of polynuclear aromatic hydrocarbons in tobacco smoke

Abstract: The research Group is ERA 553 of the CNRS. This work was carried out with financial support of DGRST (Grant No 73.7.1215).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
4

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 20 publications
0
46
0
4
Order By: Relevance
“…It also was found in the carbon black extracts [2] , coal [2] , kerosene [2] , tobacco pyrolyzate [3] , baccy pyrolysis [4] , combustion of lumber [5] , biomass [6] , and rubber [7] . Krishnan and Hites [8] had identified it by means of gas chromatograph mass spectrometry and coelution of standard acephenanthrylene.…”
mentioning
confidence: 92%
“…It also was found in the carbon black extracts [2] , coal [2] , kerosene [2] , tobacco pyrolyzate [3] , baccy pyrolysis [4] , combustion of lumber [5] , biomass [6] , and rubber [7] . Krishnan and Hites [8] had identified it by means of gas chromatograph mass spectrometry and coelution of standard acephenanthrylene.…”
mentioning
confidence: 92%
“…The condensate from 90 cigarettes was collected in two dry-ice traps, the last containing a glass wool plug. The PAH were isolated from the cigarette smoke condensate (CSC) using the separation and gas chromatography (GC) method of Severson et al (1976), shown in Figure 1.…”
Section: Use Of Pale-yellow Tobacco To Reduce Smoke Polynuclear Aromamentioning
confidence: 99%
“…1-MP levels in cigarette smoke condensate vary between 4.1 and 36.2 g/100 cigarettes, which is about three to ten times higher compared to benzo[a]pyrene levels in eight different brands of cigarettes (Grimmer, 1979;Lee et al, 1976;Severson et al, 1976). Substantial amounts of 1-MP were also detected in exhausts of diesel engines (Jensen and Hites, 1983), in restaurants and pubs (Husgafvel-Pursiainen et al, 1986), as contaminant in smoked cheese and olive oil , and as bio-accumulated pollutant in sea products (Pancirov and Brown, 1977).…”
Section: Introductionmentioning
confidence: 98%